Pegilodecakin combined with pembrolizumab or nivolumab for patients with advanced solid tumours (IVY): a multicentre, multicohort, open-label, phase 1b trial. Issue 11 (November 2019) - Naing, Aung; Wong, Deborah J; Infante, Jeffrey R; Korn, W Michael; Aljumaily, Raid; Papadopoulos, Kyriakos P; Autio, Karen A; Pant, Shubham; Bauer, Todd M; Drakaki, Alexandra; Daver, Naval G; Hung, Annie; et al.
Summary: Background: IL-10 has anti-inflammatory and CD8+ T-cell stimulating activities. Pegilodecakin (pegylated IL-10) is a first-in-class, long-acting IL-10 receptor agonist that induces oligoclonal T-cell expansion and has single-agent activity in advanced solid tumours. We assessed the safety and activity of pegilodecakin with anti-PD-1 monoclonal antibody inhibitors in patients with advanced solid tumours. Methods: We did a multicentre, multicohort, open-label, phase 1b trial (IVY) at 12 cancer research centres in the USA. Patients were assigned sequentially into cohorts. Here, we report on all enrolled patients from two cohorts treated with pegilodecakin combined with anti-PD-1 inhibitors. Eligible patients were aged at least 18 years with histologically or cytologically confirmed advanced malignant solid tumours refractory to previous therapies, and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients with uncontrolled infectious diseases were excluded. Pegilodecakin was provided in single-use 3 mL vials and was self-administered subcutaneously by injection at home at 10 μg/kg or 20 μg/kg once per day in combination with pembrolizumab (2 mg/kg every 3 weeks or 200 mg every 3 weeks) or nivolumab (3 mg/kg every 2 weeks or 240 mg every 2 weeks or 480 mg every 4 weeks at the approved dosing), both of which were given intravenously at the study site. Patients received pembrolizumab or nivolumab with pegilodecakin until disease progression, toxicity necessitating treatment discontinuation, patient withdrawal of consent, or study end. The primary endpoints were safety and tolerability, assessed in all patients enrolled in the study who received any amount of study medication including at least one dose of pegilodecakin, and pharmacokinetics (previously published). Secondary endpoints included objective response by immune-related response criteria in all patients who were treated and had evaluable measurements. The study is active but no longer recruiting, and is registered with ClinicalTrials.gov, NCT02009449 . Findings: Between Feb 13, 2015, and Sept 12, 2017, 111 patients were enrolled in the two cohorts. 53 received pegilodecakin plus pembrolizumab, and 58 received pegilodecakin plus nivolumab. 34 (31%) of 111 patients had non-small-cell lung cancer, 37 (33%) had melanoma, and 38 (34%) had renal cell carcinoma; one (<1%) patient had triple-negative breast cancer and one (<1%) had bladder cancer. Data cutoff was July 1, 2018. Median follow-up was 26·9 months (IQR 22·3–31·5) for patients with non-small-cell lung cancer, 33·0 months (29·2–35·1) for those with melanoma, and 22·7 months (20·9–27·0) for those with renal cell carcinoma. At least one treatment-related adverse event occurred in 103 (93%) of 111 patients. Grade 3 or 4 events occurred in 73 (66%) of 111 patients (35 [66%] of 53 in the pembrolizumab group and 38 [66%] of 58 in the nivolumab group), the most common of which were anaemia (12 [23%] in the pembrolizumab group and 16 [28%] in the nivolumab group), thrombocytopenia (14 [26%] in the pembrolizumab group and 12 [21%] in the nivolumab group), fatigue (11 [21%] in the pembrolizumab group and 6 [10%] in the nivolumab group) and hypertriglyceridaemia (three [6%] in the pembrolizumab group and eight [14%] in the nivolumab group). There were no fatal adverse events determined to be related to the study treatments. Of the patients evaluable for response, objective responses were 12 (43%) of 28 (non-small-cell lung cancer), three (10%) of 31 (melanoma), and 14 (40%) of 35 (renal cell carcinoma). Interpretation: In this patient population, pegilodecakin with anti-PD-1 monoclonal antibodies had a manageable toxicity profile and preliminary antitumour activity. Pegilodecakin with pembrolizumab or nivolumab could provide a new therapeutic opportunity for previously treated patients with renal cell carcinoma and non-small-cell carcinoma. Funding: ARMO BioSciences, a wholly owned subsidiary of Eli Lilly and Company.